the fiscal strategies and the reduction of the tax evasion in the department of cajamarca to 2015 - Ojeda-Torres, Alan E. (2019)
As in the rest of the departments of Peru, in Cajamarca, Tax Evasion constitutes one of the main obstacles to the social, economic and formal development of our cities, in this sense the National Superintendence of Tax Administration has implemented strategies prosecutors of a massive nature to reduce evasion gaps. The main objective of the present investigation was to evaluate the impact of these fiscal strategies in the tax evasion reduction and the specific objectives were to confirm the reduction of tributary gaps such as veracity, declaration and documentary. Being the study prepared in the Department of Cajamarca during 2015, the methods used to develop the research were mainly two ones: First the surveys about the perception of the taxpayers that were audited, as well as also the statistical analysis of historical data regarding the impact that said strategies had on the tax behavior of the taxpayers investigated. The results were positive and showed that both from the perception of the taxpayers reflected in their answers to the questionnaire, as well as in the historical analysis of their studied data after having been audited, it shows that tax strategies of a massive nature or known as "Operational Control Actions" they are very efficient and reduce tributary gaps like: veracity, declaration and documentary.Key Words: Brechas de Evasión, Superintendencia Nacional de Administración Tributaria, Acciones de Control Operativo, Contribuyentes, Recaudación.